2014
DOI: 10.12968/bjhc.2014.20.7.330
|View full text |Cite
|
Sign up to set email alerts
|

Innovating care in the community

Abstract: The move to care in the community is a key feature of NHS policy aimed at delivering better care while reducing costs. A multi-award-winning service in Oxford is leading the way in innovative community care, making a real difference to improving patient health and wellbeing. The Oxford Emergency Multidisciplinary Unit in Abingdon, Oxford was set up to meet the urgent assessment and treatment needs of patients with multiple, often complex problems, many of whom are frail and elderly. The unit provides comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The provision of tailored bed-based in-patient care for frail adults as a direct alternative to treatment on a general medical ward was described in 32 articles derived from 24 studies. This included 8 articles [15][16][17][18][19][20][21][22] reporting results from 6 randomised controlled trials, 1 trial protocol without results [23], 11 observational studies with a comparator group reported across 15 articles [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and 8 descriptive studies without a comparator [39][40][41][42][43][44][45][46]. A detailed description of the care models is provided in Supplementary Table 2A.…”
Section: Bedded Acute Frailty Units Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of tailored bed-based in-patient care for frail adults as a direct alternative to treatment on a general medical ward was described in 32 articles derived from 24 studies. This included 8 articles [15][16][17][18][19][20][21][22] reporting results from 6 randomised controlled trials, 1 trial protocol without results [23], 11 observational studies with a comparator group reported across 15 articles [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and 8 descriptive studies without a comparator [39][40][41][42][43][44][45][46]. A detailed description of the care models is provided in Supplementary Table 2A.…”
Section: Bedded Acute Frailty Units Modelsmentioning
confidence: 99%
“…The mean number of beds in each unit was 18 (SD 8). The number of beds was not reported in 3 studies [25,41,46]. A mobile model providing specialist consultations to patients within general medical bed was described in 3 studies [20,33,36] (and an integrated service with variable bed capacity operating within an acute medical unit in 1 study [45].…”
Section: Bedded Acute Frailty Units Modelsmentioning
confidence: 99%